Matt Nichol: Globalization, Sports Law and Labour Mobility: The Case of Professional Baseball in the United States and Japan - Burch, Micah (Zeitschrift für Japanisches Recht, 2021)
Edward Elgar Publishing, Cheltenham, UK and Northampton, MA, USA 2019, vii + 245 pp. (203 pp. + Bibliography & Index), ca. 125 US, ISBN: 978-1-78811-500-1